Compliance with DMPA contraceptive injection repeat visits during the Covid 19 pandemic - Gita Nirmala Sari; Ananda Putri Setiawan; Novita Rina Antarsih; Yulia Sari; Yudhia Fratidhina; Li Yuting; Eprila Eprila (Journal of Health Technology Assessment in Midwifery, 2022)
The 3-month of DMPA injectable contraceptive is one of the contraceptive methods that has decreased in the number of users during the Covid-19 pandemic. Acceptors of 3-month injectable contraceptives who do not comply with visits can reduce effectiveness and increase the risk of pregnancy. This study aims to examine the factors that influence the adherence of 3-month DMPA injection family planning acceptors during the Covid-19 pandemic. This was quantitative research with cross sectional design. The sample used in this study were 125 acceptors of 3-month DMPA injection family planning. Data was obtained by using a questionnaire. The analysis was performed using logistic regression. Based on multivariate analysis, there were 3 factors associated to adherence to DMPA injection repeat visits, namely family planning acceptor occupation　(OR=0.11, 95%CI= 0.04-0.31), knowledge (OR=3.59, 95%CI=1.34-9.58) and husband's support (OR=5.84, 95%CI=2.42-14.08). The most dominant factor was husband's support (OR=6.65, 95%CI=2.51-21.46). Husband's support is the most important factor that is strongly associated to injection repeat visits for DMPA family planning acceptors during the covid 19 pandemic. Good communication between partners is needed to increase DMPA injection repeat visits.